INNOVATIVE WORK BEHAVIOUR OF GENERATION Z EMPLOYEES IN CIKARANG - Mahmudah, Siti; Hindarwati, Enny Noegraheni (Jurnal Ilmiah Ekonomi Bisnis, 2025)
In today's employment, Generation Z has taken centre stage in almost every industry. Examining the effects of information sharing, employee engagement, and transformational leadership on the creative work practices of Generation Z employees in Cikarang was the goal of this study. A sample of 320 respondents was obtained by distributing questionnaires to Generation Z employees in the area using an associative design and quantitative approaches. The results showed that knowledge sharing, employee engagement, and transformational leadership all had a favourable impact on the creative work practices of Cikarang's Generation Z workforce.